(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This paper explores the crucial role of motivation in enhancing an individual’s ability to perform special skills effectively on stage. Motivation acts as the driving force that transforms potential into performance, enabling individuals to overcome fear, anxiety, and self-doubt. The study highlights different forms of motivation such as intrinsic and extrinsic and how they influence stage performance in various artistic fields including music, dance, drama, and public speaking. Practical examples demonstrate that motivated performers tend to show higher confidence, better emotional expression, and stronger audience engagement. Furthermore, the paper discusses strategies to develop and maintain motivation through goal setting, self-reflection, mentorship, and positive feedback.